Elemental and Organic Matrix Analysis of the Land Snails Monacha cartusiana and Cochlicella barbara Shells - Rahman, Hero S.; Raheem, Dotsha J.; Hussen, Fenik Sh.; Karim, Hawbash H.; Khudhur, Shelan M.; Chaqmaqchee, Faten A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
In this study, the occurrence of two introduced terrestrial gastropod species: Monacha cartusiana (O.F. Müller, 1774) and Cochlicella barbara (Linnaeus, 1758), in the Kurdistan Region of Iraq, was investigated. Species identifications were made based on snail morphology. Snail shells were studied to determine their chemical composition and its effect on their success and establishment in the study area. Their organic components (protein and chitin) and inorganic matrix (elements) were analyzed and their correlations were investigated. Elemental analysis was performed using inductively coupled plasma - mass spectrometry and energy dispersive X-ray fluorescence for both species and their surrounding soil. Gravimetric analysis revealed that the main shell component was calcium carbonate (CaCO3) in the form of aragonite, comprising over 96% of the shells’ mass. Proteins and carbohydrates accounted for <4% of the shells. Fourier-transform infrared spectroscopy spectral analysis confirmed the presence of chitin in its β-allomorph form. Thirty-eight elements were detected. Of which, potassium (K), strontium (Sr), and rhenium (Re) were significantly different between the two species. A highly significant correlation was found between protein and carbohydrates, and CaCO3 indicating the role of the organic matrix in the formation of the mineral component. The survival of the studied species is partly attributed to a considerable overlap in their organic and inorganic chemical characteristics, along with notable differences.